Theorising the Ibero-American Atlantic - Braun, Harald E. (Harald Ernst); Vollendorf, Lisa (Medieval and early modern Iberian world ;, 2013)
Theorising the Ibero-American Atlantic offers fresh and challenging perspectives on the Atlantic turn in Hispanic and Latin American studies. Contributors, while mindful of its limits, explore and establish the viability and value of the Ibero-American Atlantic as a framework of enquiry.